1992
DOI: 10.1007/bf00994360
|View full text |Cite
|
Sign up to set email alerts
|

Attraction of male turnip mothsAgrotis segetum (Lepidoptera: Noctuidae) to sex pheromone components and their mixtures at 11 sites in Europe, Asia, and Africa

Abstract: Selected combinations of (Z)-5-decenyl, (Z)-7-dodecenyl, and (Z)-9-tetradecenyl acetates, the pheromone components of the turnip mothAgrotis Segetum were tested for field attractancy at six, two, and three sites in Europe, Asia, and Africa, respectively. At all of the sites in Eurasia and in northern Africa the ternary mixture of the acetates captured most males, while at the sites south of the Sahara in Africa, (Z)-5-decenyl acetate alone was responsible for attraction. Differences in male attraction among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
6

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 17 publications
0
37
0
6
Order By: Relevance
“…The turnip moth, Agrotis segetum, is widely distributed throughout Europe, the near East, and Africa. Various ratios of (Z)-5-decenyl acetate, (Z)-7-dodecenyl acetate, and (Z)-9-tetradecenyl acetate were required to attract males throughout Eurasia and North Africa, whereas in sub-Saharan Africa, (Z)-5-decenyl acetate alone attracted males (Arn et al 1983;Löfstedt et al 1986;Tóth et al 1992;Wu et al 1999). The larch budmoth, Zeiraphera diniana, consists of two host races that feed on larch and Cembran pine in the European Alps.…”
Section: Discussionmentioning
confidence: 99%
“…The turnip moth, Agrotis segetum, is widely distributed throughout Europe, the near East, and Africa. Various ratios of (Z)-5-decenyl acetate, (Z)-7-dodecenyl acetate, and (Z)-9-tetradecenyl acetate were required to attract males throughout Eurasia and North Africa, whereas in sub-Saharan Africa, (Z)-5-decenyl acetate alone attracted males (Arn et al 1983;Löfstedt et al 1986;Tóth et al 1992;Wu et al 1999). The larch budmoth, Zeiraphera diniana, consists of two host races that feed on larch and Cembran pine in the European Alps.…”
Section: Discussionmentioning
confidence: 99%
“…Geographical variation has been found both in female signals [34][35][36][37] and male responses [22,23,38]. This suggests that moth sex pheromone signals and behavioural responses are affected by local environmental factors, although this variation may also be due to environmentally independent sexual selection.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that geographic variations in the pheromone system are present within the Philippines as previously reported with the sex pheromones of other species such as Agrotis segetum (Tóth et al, 1992), if Ramachandran et al used a population of another locality in the Philippines for their pheromone identification. This also might indicate the occurrence of pheromone-based assertive mating or random mating as has been 486 K. KAWAZU et al found with population using different pheromone blends of Ostrinia scapulalis (Takanashi et al, 2005).…”
Section: Discussionmentioning
confidence: 96%